2009
DOI: 10.1248/bpb.32.976
|View full text |Cite
|
Sign up to set email alerts
|

The Promoting Activity on Human Megakaryocytopoiesis and Thrombopoiesis by Liquid Crystal-Related Compounds

Abstract: The liquid crystal compounds have a common structure with the cell membrane, having both a hydrophilic and hydrophobic residue, thus suggesting an affinity to the cell membrane. However, little information regarding a biological effect by liquid crystal compounds has been reported. In order to view the biological potential of liquid crystal compounds, the present study evaluated the in vitro human hematopoietic promoting effects by 18 liquid crystal-related compounds. In particular, these compounds are evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, compound 9 did not affect the cell cycle distribution and these pathways, and the mechanism of cell growth suppression by compound 9 remains unclear. In our previous study, we showed the promoting activity of LCRCs on human megakaryocytopoiesis and thrombopoiesis [16]. The mechanisms between the previous and present studies seem to be different because each effective compound and dose was different.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, compound 9 did not affect the cell cycle distribution and these pathways, and the mechanism of cell growth suppression by compound 9 remains unclear. In our previous study, we showed the promoting activity of LCRCs on human megakaryocytopoiesis and thrombopoiesis [16]. The mechanisms between the previous and present studies seem to be different because each effective compound and dose was different.…”
Section: Discussionmentioning
confidence: 50%
“…Generally, the liquid crystal is synthesized from various precursors, such as a flexible chain, a rigid aromatic core, and hydrophobic and hydrophilic units. Our previous study showed that these precursors, namely liquid crystal-related compounds (LCRCs), exhibited a promoting activity on human megakaryocytopoiesis and thrombopoiesis [16]. However, the possible use of LCRCs as an antitumor drug remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Serum-free medium Stem-pro (10639-011) and Dynal CD34 C Isolation kit (11301D) was purchased from Invitrogen. All human recombinant growth factors, such as TPO (300-18), SCF (300-07), IL-3(200-03), IL-6(200-06), and Flt-3 (300- 19) were purchased from Peprotech Inc. The 2 poly-unsaturated fatty acids arachidonic acid (AA (A3555)) and Docosahexanoic acid (DHA (D2534).)…”
Section: Reagentsmentioning
confidence: 99%
“…TPO is the primary regulator of megakaryopoiesis [16][17] whereas SCF, FLT-3, IL-3, IL-6 and IL-11 act as secondary regulators. 18 In attempts to further increase the efficiency of in vitro production of MKs and platelets various investigators have used additives like liquid crystal related compounds, 19 nicotinamide (vitamin B3), 20 heparin, 21 proteoglycans, 22 prostaglandins like 15-deoxy-delta-PGJ2. 23 Some investigators have used extracellular adhesive proteins like fibrinogen, fibronectin and VWF 24 to enhance platelet production.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on the structural affinities of cell membranes for LCs and have assessed the application of LCs as drug-delivery systems [ 17 , 18 ]. In previous studies, we investigated the cytotoxicity of LC compounds and their precursors (mesogenic compounds) [ 19 23 ] and showed that some amphiphilic LC compounds, such as cyanobiphenyl derivatives with terminal hydroxyl moieties, moderately suppressed cell growth in the NSCLC cell line A549 [ 20 ]. Furthermore, an amphiphilic LC precursor with three aromatic rings dramatically suppressed cell growth and induced apoptosis in A549 cells, but it also showed low cyototoxicity in normal WI-38 fibroblast cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%